Assessment instruments to evaluate sexual function and satisfaction of pregnant women in prenatal health care context: scoping review protocol - Alexandra Tereso; Alice Curado; Ana Brantes; Ricardo Antunes (Nursing Research, Innovation and Development Centre of Lisbon (CIDNUR) of the Nursing School of Lisbon (ESEL), 2024)
Introduction Despite the fears and beliefs related to sexual function and satisfaction during pregnancy, the healthy experience of sexuality (which is not reduced to these aspects but encompasses them) is relevant to women. Although quality of life is associated with sexual function and satisfaction, the effect of pregnancy in those dimensions, needs to be further explored in order to prevent problems and respond appropriately to women needs.   Objective This scoping review aims to map, in the scientific literature, the assessment instruments to evaluate the sexual function and sexual satisfaction of pregnant women in prenatal health care context. Methods The Joanna Briggs Institute guidelines are used to conduct this protocol. The key information sources to be searched include several databases, such as MEDLINE, CINAHL, MedicLatina, Pubmed, Web of Science, Google Scholar and Open Access Scientific Repository of Portugal. Quantitative, qualitative, or mixed studies and secondary studies published in Portuguese, English, Spanish, French, and between 2018 and 2023 will be included. For inclusion criteria will be considered studies referring to instruments to evaluate sexual function and satisfaction of pregnant woman 18 years or over, in prenatal health care context [Population Concept Context framework]. Titles and abstracts of identified citations will be screened independently and assessed for eligibility by two reviewers. Potentially relevant full-text studies and data will be extracted using a data extraction form. The extraction table will show the data mapped in a descriptive way responding to research questions. Selected documents by each reviewer will be uploaded to the Covidence web tool, to optimize the systematic review process and facilitate collaboration between reviewers. For the management of references, the Mendeley software will be used. Discussion Mapping the instruments will enable to summarize the valid, reliable, and specific assessment instruments, their possibilities, and limitations. This results, will contribute to improve the access to information about sexual function and satisfaction during pregnancy, to identify women needs, and plan specific health care interventions. The outcomes relevance will help to guide health professionals and researchers to use the most appropriate assessment tools in prenatal health care context. Systematic review registration Open Science Framework - registration number: osf.io/csg8t